Exchange rates and the balance of payments: Reconciling an inconsistency in Post Keynesian theory. Issue 3 (3rd July 2019) - Harvey, John T.
Abstract: There already exist Post Keynesian alternatives to neoclassical trade and exchange rate theories. That focusing on the former explains the direction of trade as a function of absolute advantage, which is, in turn, driven by cost and technological differences. There is no automatic force causing these differences to diminish over time meaning that—unlike in Orthodoxy—it is possible for trade imbalances to be large and long-lasting. Meanwhile, Post Keynesian exchange rate theory argues that currency prices are set almost entirely by autonomous financial capital flows. If international investors' forecast of profit from dollar-denominated assets improves, they buy dollars and the dollar appreciates. On the surface of it, these appear to be satisfactory real world-based approaches that offer much more explanatory power than comparative advantage, purchasing power parity, et cetera. When viewed together, however, an inconsistency emerges—for, a theory that is predicting the trade balance is simultaneously predicting the capital account balance (and the exchange rate at which these transactions are occurring). If Post Keynesian scholarship suggests that a particular nation would have the absolute advantage and should be experiencing a trade surplus, then it must also argue that autonomous capital flows will cooperate and create a corresponding deficit. But Post Keynesian exchange rate theorists see absolutely no reason to expect the latter except by coincidence. Although a tentative solution to this problem has been forwarded, it conflicts with other well-established Post Keynesian tenets. The goal of this article is to resolve the matter once and for all and by a means that leaves all the essential conclusions unchanged. The key lies in explicitly modeling the manner in which trade flows are financed. Once it is acknowledged that the necessary liquidity is endogenously created and that they do not have any direct impact on currency prices, then it is possible to show that trade flows are a function of absolute advantages while exchange rates are driven by international finance.